Occurrence of fatalities in mountaineering: The case of Mt. Kenya - Nkatha Muthomi; Lucy-Joy Wachira; Shikuku Willy Ooko (Cogent Social Sciences, 2023)
A fatality is the most detrimental incident that can occur in mountaineering. It is important to study previous cases and learn from circumstances surrounding fatal incidences in programmes sharing some common elements. This paper is set to investigate the occurrences of fatal incidences in mountaineering, the case of Mt. Kenya. It captures the qualitative findings on fatality occurrences. Respondents consisted of porters, guides, instructors, facilitators and key stakeholders involved in outdoor adventure activities on Mt. Kenya. The study used snowballing approach to identify the participants. Focus group discussions involving 52 respondents were conducted, in-depth interviews took place with four key informants and additional records were sought through desk reviews. The study found out that occurrence of fatalities was not well documented in a structured database. Deep grieving and regrets were noted. Predisposing factors leading to fatalities during mountaineering included; The “I MUST summit mentality”, lack of proper acclimatization, lack of visitor education, and lack of early diagnosis of altitude sicknesses. With the inherent risks and dangers that lead to fatalities in the mountaineering industry, the study recommends the need for providers to be keen on risk assessment and management as well as develop response strategies for various eventualities.